Positive association between omega-3/6 polyunsaturated fatty acids and idiopathic normal pressure hydrocephalus: a mendelian randomization study - Li, Jilai; Huang, Ning; Zhang, Xiang; Peng, Jie; Huang, Qin (Frontiers in Genetics, 2023)
Background: Idiopathic normal pressure hydrocephalus (iNPH) is a common disease among the elderly, which brings great harm to the health of patients and imposes a huge economic burden on the health care system. Research has shown that it is possible to prevent iNPH through nutritional and dietary interventions. Intake of omega-3 and omega-6 polyunsaturated fatty acids (PUFAs) can reduce the risk of many diseases. In this study, we aimed to explore the association between omega-3/6 PUFAs and iNPH. Methods: We conducted a two-sample Mendelian randomization (MR) study using summary data from publicly available genome-wide association studies (GWAS) to evaluate the potential impact of omega-3 and omega-6 PUFAs on the risk of iNPH in European populations. Inverse variance weighting was used as the main method for MR analysis, with Wald ratio, weighted median, MR-Egger, simple mode, and weighted mode as supplementary methods. In addition, we performed a series of instrument variable strength evaluations and sensitivity analyses to test the reliability of the study results. Finally, we also conducted a linkage disequilibrium score regression (LDSC) analysis to assess the genetic correlation and distinguish between causal associations and shared genetic variants between PUFAs and iNPH. Results: One SD increase in genetically predicted levels of total omega-3 PUFAs (OR: 0.748; 95% CI: 0.597 - 0.937; p = 0.012; IVW), DHA (OR: 0.709; 95% CI: 0.532 - 0.945; p = 0.019; IVW), ALA (OR: 0.001; 95% CI: 1.17E-06 - 0.423; p = 0.026; Wald ratio), and DHA (OR: 0.709; 95% CI: 0.532 - 0.945; p = 0.019; IVW) were associated with a reduced iNPH risk. LDSC did not reveal any significant genetic correlations. Conclusions: Higher genetically predicted levels of total omega-3 PUFAs, ALA, DHA, and DPA are associated with a reduced risk of iNPH. These findings have important implications for preventing iNPH and future nutritional guidance.